HYPERURICEMIA AS A PREDICTOR OF CHRONIC HEART FAILURE - M. V. Ledyakhova; S. N. Nasonova; S. N. Tereshchenko (Столичная издательская компания, 2015)
Aspects of comorbidity in patients with chronic heart failure are discussed. A focus on hyperuricemia, its effect on the course and prognosis in patients with heart failure, as well as the possibility of its medical correction are maintained.